THE IMPLEMENTATION OF A CARBON TAX WITHIN THE INDONESIAN TAX LEGAL SYSTEM: A LITERATURE REVIEW FOLLOWING THE ENACTMENT OF THE HPP ACT - Gunawan Widjaja (ADISAM Publisher, 2026)
This study examines the implementation of carbon tax within the Indonesian tax law system following the Tax Regulation Harmonisation Act. Carbon tax serves as a fiscal instrument that not only functions to increase state revenue but also to control greenhouse gas emissions through the internalisation of external costs arising from carbon-emitting activities. This study employs a literature review using a normative legal approach to examine the legal framework of the carbon tax, the challenges to its implementation, and its prospects in supporting the transition towards low-carbon development. The findings indicate that the HPP Act has provided an important initial legal foundation; however, the implementation of the carbon tax still faces obstacles in the form of unclear technical standards, institutional readiness, inter-sectoral coordination, and potential economic and social impacts. On the other hand, a carbon tax holds great promise as an environmental policy instrument if supported by clear secondary legislation, a robust monitoring system, and fair compensation mechanisms. Thus, a carbon tax has the potential to become an important part of tax reform aligned with Indonesia’s sustainable development goals.